The Effect of Dayak Onion Extract on Lactic Acid Levels in Mice with FST Model - Aulia Ramadhani; Muchsin Doewes; Shanti Listyawati (Global Health Science Group, 2023)
Intense physical exercise can increase lactic acid levels in the blood as a result of the anaerobic metabolism that occurs at that time. The impact of increased levels of lactic acid includes the occurrence of acidosis, damage to body cells, and fatigue which reduces muscle performance. Antioxidants can play a role in preventing body fatigue caused by oxidative stress. Onion Dayak (Eleutherine palmifolia) is a type of medicinal plant that is useful for health. The high content of antioxidants in Dayak onions can be used as an alternative anti-fatigue ingredient. This study aimed to look at the effect of the dose and duration of Dayak onion extract on lactic acid levels and physical activity in mice forced swimming test models. Type of Research Randomized Pre and Post-Test Control Group Design. Male White Mice (Sprague Dawley) 2 months old (weight 150-200g). Divided into 5 groups K- (the experimental group was not given Dayak onion extract, they were still given FST), K+ (the experimental group was given xanthine and FST), P1 (given Dayak onion extract at a dose of 50mg/200gBW), P2 (given the extract onion Dayak dose of 100mg/200gBB), P3 (given onion extract dose of 200mg/200gBW). Dayak onion extract was given for 28 days and given the forced swimming test, then the changes in lactic acid and physical activity endurance in swimming were observed.